(untitled) (diségno, 2026)
Guillem Sagrera is an essential architect during the 15th century in the Crown of Aragon. He is known for his participation in the construction of Mallorca Cathedral, first as an apprentice in the Portico del Mirador, from 1397 and later as a teacher. He was also commissioned to build the Lonja (Maritime Exchange) in Mallorca, begun in 1426. In this period his residence in Perpignan is documented, at least from 1410, but there are certain unknowns about the works in which he may have participated in Roussillon during this period, such as his part in the Lonja del Mar, in Perpignan or the chronology in the works of the chapterhouse of Saint John the Baptist. This period influenced and modified the way of conceiving the geometric layout of the structure in his buildings. This study aims to determine two aspects: 1. Through the parallelisms in his sculpture, to determine the works that he was able to carry out in this period in Roussillon. 2. Once his participation in the Chapterhouse of Saint John the Baptist was confirmed, to carry out a deep graphic analysis, modelling the architectural space, in which the structural and geometric experimentation is confirmed, observing how there was a change from the southern Gothic layout, eliminating capitals and corbels, to a freer layout with a mastery of the geometric layout, going beyond the canons and how this would be reflected in two of his later works, the Lonja de los Mercaderes in Palma and the Sala dei Baroni, in Castell Nuovo in Naples.